Development of Electronic Parking System using RFID(Radio Frequency Identification) Technology in UMS Area - Kurniawan, Rizky, Gunawan Ariyanto, Ph.D, Agus Ulinuha, ST., MT., Ph.D (2014)
Currently, there are many identification using RFID (Radio Frequency Identification) technology, the application of this technology has helped many people to work. One application of RFID is an automatic parking system. It can be used for parking access in and out automatically which can help users to access in and out of parking at UMS. In UMS which is currently still using the parking system where each user manually out of the parking area, then the user will show as a vehicle registration validation, with such a way that would make any long queue again at rush hour. With this system, it is necessary to allow the solution to solve problems, such as the use of RFID technology. The author use Passive RFID, the maximum range with the RFID tag is about 5cm-10cm, communication speed 106Kbit/s, frequency 125 KHz, plug and play system, and support operating system windows 95/98/200/XP/windows 7/Linux and windows 8. The purpose of this research is to improve the effectiveness, efficiency and security in UMS, because each user will be given a card and the card contains a user's data access in and out of parking to the parking area UMS. These studies used several methods such as direct interviews with park guards, reading literature and get a needs analysis helps researchers to make program management applications. The result of this study is a desktop application for a microcontroller and a web-based information system to access data and reports parking that can help users to see the data and can see the parking lot parking reports each month and can create a policy to build more parking space again and also allows users to access and out of the parking lot which is no longer automatically using registration for access in and out of parking, but parking UMS user is given a card containing a parking user data, and is no longer using the vehicle registration for access in and out.